144k views
4 votes
−5x + y = −3
3x − 8y = 24

User Allen Pike
by
5.5k points

2 Answers

0 votes

Answer:

- 5x + y =-3 ......1

3x -8y = 24.........2

eqn 1 is multiply by 8 .we get -40 x +8y=-24 .....3

-40 x +8 y =-24 ...........3

3 x - 8y = 24 ......... 2

·································

-37 x +0 = 0

··························

x =0

put x = 0 in equation 2

3 x -8 y =24

3×0 -8 y = 24

0 -8 y=24

-y =24÷8

-y =3

y = -3

ans ;

x = 0

y = -3

Explanation:

User JuneT
by
5.7k points
9 votes

Answer:

x = 0

y = -3

Explanation:

-5x + y = -3 --------------(I)

3x - 8y = 24 ------------(II)

Multiply the equation (I) by 8

(I)*8 - 40x + 8y = -24

(II) 3x - 8y = 24 {Add and y will be eliminated}

-37x = 0

x = 0

Plugin x = 0 in equation(I)

-5*0 + y = -3

0 + y = -3

y = -3

User Gyo
by
6.2k points